Industry dynamics and high-growth firms' contribution to productivity growth - Márta Bisztray; Francesca De Nicola; Balázs Muraközy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
This paper investigates the contribution of high-growth firms (HGFs) to aggregate productivity growth. Four stylized facts emerge. First, HGFs mainly contribute to productivity growth during their high-growth phase but not afterwards. Second, their contribution varies substantially across industries and it is not necessarily positive. Third, the impact on productivity depends on how HGFs are defined. Output-based HGFs substantially outperform employment-based ones in terms of their productivity contribution while the difference in terms of job creation is low. Fourth, HGFs' contribution to productivity is higher in industries where industry dynamics favor growing firms, captured by the strength of reallocation and the relationship between productivity growth and size growth. We present a simple model to show that these patterns arise naturally under realistic correlation structures. Our results suggest that policies supporting HGFs may focus on firms increasing their sales, and these can effectively be complemented by framework policies promoting efficient reallocation.
Keywords: L25; O40; 330; high-growth firms; productivity growth; reallocation; industry dynamics